Sustainable development goals and ending ECC as a public health crisis - Saikia, Ankita; Aarthi, Jagadeesan; Muthu, MS; Patil, Sneha S.; Anthonappa, Robert Prashanth; Walia, Tarun; Shahwan, Moayad; Mossey, Peter; Dominguez, Monica (Frontiers in Public Health, 2022)
Early Childhood Caries (ECC) remains a global issue despite numerous advancements in research and interventional approaches. Nearly, 530 million children suffer from untreated dental caries of primary teeth. The consequences of such untreated dental caries not only limit the child's chewing and eating abilities but also, significantly impact the child's overall growth. Research has demonstrated that ECC is associated with nearly 123 risk factors. ECC has also been associated with local pain, infections, abscesses, and sleep pattern. Furthermore, it can affect the child's emotional status and decrease their ability to learn or perform their usual activities. In high-income countries, dental care continues to endorse a “current treatment-based approach” that involves high-technology, interventionist, and specialized approaches. While such approaches provide immediate benefit at an individual level, it fails to intercept the underlying causes of the disease at large. In low-income and middle-income countries (LMICs), the “current treatment approach” often remains limited, unaffordable, and unsuitable for the majority of the population. Rather, dentistry needs to focus on “sustainable goals” and integrate dental care with the mainstream healthcare system and primary care services. Dental care systems should promote “early first dental visits,” when the child is 1 year of age or when the first tooth arrives. The serious shortages of appropriately trained oral healthcare personnel in certain regions of the world, lack of appropriate technologies and isolation of oral health services from the health system, and limited adoption of prevention and oral health promotion can pose as critical barriers. The oral health care systems must focus on three major keystones to combat the burden of ECC−1. Essential oral health services are integrated into healthcare in every country ensuring the availability of appropriate healthcare accessible and available globally, 2. Integrating oral and general healthcare to effectively prevent and manage oral disease and improve oral health, 3. Collaborating with a wide range of health workers to deliver sustainable oral health care tailored to cater to the oral health care needs of local communities.